Undifferentiated connective tissue dysplasia and respiratory diseases in children and adolescents (review of literature) - O.M. Voloshin; O.Yu. Chumak (Zaslavsky O.Yu., 2017)
Connective tissue dysplasia is widespread genetically determined disturbance of this tissue development in the process of intrauterine and postnatal ontogenesis which is characterized by the defects of its fibrous structures and ground substance. The indicated changes result in homeostasis derangements in tissues, organs and organism as a whole. They manifest themselves by different external, visceral and locomotor abnormalities with progressive course. The presence of connective tissue dysplasia has a considerable influence on the peculiarities of associated diseases as well as pharmacokinetics and pharmacodynamics of medicines which are used for treatment of these diseases. Nowadays, they distinguish differentiated (classified, monogenic) and undifferentiated (unclassified, multifactorial) forms of connective tissue dysplasia. Simultaneous respiratory diseases in children and adolescents are still one of the most urgent medical and social problem that is determined by their high incidence, complicated diagnosis and the risk of chronic respiratory pathology development. Therefore, scientific researches regarding the mechanisms and degree of connective tissue dysplasia influence on the appearance and course of respiratory diseases are well-grounded. According to the literature sources, acquired respiratory diseases in children and adolescents against the background of undifferentiated connective tissue dysplasia have considerably more severe and prolonged clinical signs with impaired effectiveness of traditional treatment. They are inclined to untypical and recurrent course and more frequent and more severe complications as well. However, the direction of such influence in the process of child development remains largely undefined. It should be noted that the majority of scientific researches on the combination of connective tissue dysplasia and respiratory diseases has been carried out among school-age children and adolescents. In this connection, the early prediction of connective tissue dysplasia in infants and small children, when its external manifestations are infrequent and ill-defined, seems quite promising. The detection of systemic connective tissue dysplasia exactly on the early stages of postnatal ontogenesis can be a ground for timely and purposeful administration of some appropriate preventive measures.